Environment-friendly carbon-free tundish dry material

By using polysucrose/gelin hydrogel composite material and aqueous sodium silicate as binding agents in the sacking dry material and adding modified explosion-proof fibers, the problems of pollution and poor anti-scrubbing performance caused by phenolic resin are solved, and the problem of poor anti-scrubbing performance is achieved. High bond strength, environmental protection and durability.

CN119504234AInactive Publication Date: 2025-02-25ZHEJIANG JUANTUO NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411679434.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing tundra dry material uses phenolic resin as a binding agent, which leads to harmful and irritating gases during baking, pollutes the environment, and has poor anti-erosion and erosion erosion performance at high temperatures.

Method used

New environmentally friendly binding agents, including polysucrose/gelatin hydrogel composites and aqueous sodium silicate, are used to replace solid phenolic resins, and modified explosion-proof fibers are added to the raw materials to improve anti-shrink performance.

Benefits of technology

No trace amount of irritating gas is generated or generated during the baking process, which improves the bonding strength of the material and anti-shrinkage performance, extends the service life, and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147924040000031
    Figure BDA0005147924040000031
  • Figure BDA0005147924040000032
    Figure BDA0005147924040000032
  • Figure BDA0005147924040000033
    Figure BDA0005147924040000033
Patent Text Reader

Abstract

The invention discloses an environment-friendly carbon-free tundish dry material which comprises the following raw materials in percentage by weight: 15-20% of olivine with the particle size of 3-5mm, 20-30% of medium-grade magnesite clinker with the particle size of 1-3mm, 18-30% of light calcined magnesia powder with the particle size of 0.5-1mm, 5% of magnesite with the particle size of less than or equal to 0.08 mm, 8-15% of a binding agent with the particle size of less than or equal to 0.08 mm, 2% of sodium hexametaphosphate with the particle size of less than or equal to 0.08 mm and 0.5% of low-melting-point glass powder with the particle size of less than or equal to 0.075 mm. The novel environment-friendly binding agent is adopted to replace solid phenolic resin, no or trace irritant gas is generated in the baking process of the novel environment-friendly binding agent, other impurities are not brought into molten steel during continuous casting, ladle collapse is avoided, and the novel environment-friendly binding agent has the advantages of being high in strength, convenient to construct, easy to disintegrate, long in service life, environmentally friendly and the like; the modified explosion-proof fiber is coated with the newly synthesized antioxidant, so that the modified explosion-proof fiber has an excellent anti-oxidation function, the anti-aging capability of the explosion-proof fiber is prolonged, and the service life of a base material is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials and relates to an environmentally friendly carbon-free tundish dry material. Background Art

[0002] With the development of the world's steel production technology, the concept of tundish metallurgy, or tertiary metallurgy, has emerged. The tundish has changed from a simple steel transition container in the continuous casting system to a refining device with multiple refining functions. Tundish refining technology has also become one of the important technologies in clean steel production, and has formed a relatively independent tundish metallurgy. Therefore, refining tundish refractory materials has become the focus of world attention. my country's steel smelting technology has made great progress under the unremitting efforts of scientific and technological workers, and clean steel has also become a product that some domestic steel mills are vying for in order to win the market and international reputation. Therefore, it is necessary to develop a mature tundish dry material that meets the requirements of clean steel smelting in a timely manner.

[0003] At present, the widely used binder for magnesium dry materials in tundish is phenolic resin. After low-temperature heat treatment, phenolic resin can form a strong three-dimensional grid structure with high bonding strength. However, on the one hand, the price of phenolic resin is relatively high, which increases the cost; on the other hand, irritating gases such as formaldehyde are produced during the baking process, which pollutes the environment. The carbon and hydrogen after the resin is carbonized can significantly increase carbon and hydrogen. Secondly, the tundish dry materials work at high temperatures. While enduring high temperatures, they also endure the high-speed impact of molten steel injection. Therefore, explosion-proof fibers are added to the raw materials to prevent erosion and erosion. The thermal shock resistance, erosion resistance, and oxidation resistance of explosion-proof fibers are particularly important. Summary of the invention

[0004] The purpose of the present invention is to provide an environmentally friendly carbon-free tundish dry material to overcome the defects mentioned in the background technology that the use of phenolic resin produces a large amount of harmful and irritating gases, pollutes the environment, is not conducive to clean steel and environmental protection requirements, and the problem that the tundish dry material has poor anti-scouring and erosion resistance.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An environmentally friendly carbon-free tundish dry material comprises the following raw materials by weight percentage: 15%-20% of olivine with a particle size of 3-5mm, 20%-30% of medium-grade sintered magnesia with a particle size of 1-3mm, 18%-30% of light-burned magnesia powder with a particle size of 0.5-1mm, 5% of magnesia with a particle size of ≤0.08mm, 8%-15% of a binder with a particle size of ≤0.08mm, 2% of sodium hexametaphosphate with a particle size of ≤0.08mm, 0.5% of low-melting-point glass powder with a particle size of ≤0.075mm, and 0.1-0.3% of modified explosion-proof fiber with a length of 3-5mm.

[0007] The environmentally friendly carbon-free tundish dry material is made by the following steps:

[0008] Step A1, crushing the above raw materials;

[0009] Step A2, preparing ingredients according to the above formula;

[0010] Step A3, pouring the prepared dry material into the space between the outer wall of the tundish mold and the permanent village of the tundish, and forming it by self-flowing without vibration or ramming;

[0011] Step A4, baking at a temperature of 100° C.-220° C., and obtaining an environmentally friendly carbon-free tundish dry material after demoulding.

[0012] The binder is prepared by the following steps:

[0013] Step S1, respectively preparing a gelatin aqueous solution with a mass fraction of 4-6% and a polysucrose aqueous solution with a mass fraction of 5-7%, weighing the two solutions, mixing them at 48-50° C., stirring for 30 minutes, standing and cooling at room temperature, placing them in an acetone solution containing 0.2% (w / v) EDC (the volume ratio of acetone to water is 9:1), taking them out after 48-50 hours, and washing them with deionized water to obtain a preform;

[0014] Step S2, uniformly mixing the preform obtained in step S1 with sodium salt to obtain a binder.

[0015] Furthermore, in step S1, the mixing volume ratio of the aqueous gelatin solution and the aqueous polysucrose solution is 3.5-4:1.

[0016] Furthermore, in step S2, the weight ratio of the preform to the sodium salt is 0.5-0.8:1, and the sodium salt is one of sodium metasilicate pentahydrate and sodium metasilicate nonahydrate.

[0017] The modified explosion-proof fiber is prepared by the following steps:

[0018] Step C1, add β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and chloroform into a three-necked flask, add dichlorothionyl dropwise under nitrogen protection, raise the temperature to 48-52° C. after the addition is complete, react at this temperature for 6-7 hours, and distill under reduced pressure to obtain intermediate 1;

[0019] The reaction process is as follows:

[0020]

[0021] Step C2, add camphene and potassium thiocyanate into a three-necked flask, control the reaction temperature to 85-92° C., add 75% by mass of concentrated sulfuric acid thereto, react for 5-6 hours, cool, extract with ethyl acetate, wash with 0.5 mol / L NaHCO3 solution, and recrystallize to obtain intermediate 2;

[0022] The reaction process is as follows:

[0023]

[0024] Step C3, add intermediate 2, hydrazine hydrate with a mass fraction of 80%, and anhydrous ethanol into a three-necked flask, reflux for 35-40 minutes, cool and precipitate, and recrystallize from ethanol to obtain intermediate 3;

[0025] The reaction process is as follows:

[0026]

[0027] Step C4, adding intermediate 1, intermediate 3, potassium carbonate and toluene into a reaction kettle, reacting at a speed of 200-300 r / min and a temperature of 60-70° C. for 5-8 hours to obtain intermediate 4;

[0028] The reaction process is as follows:

[0029]

[0030] Step C5, add intermediate 4 and DMF into a three-necked flask, mix well and then add explosion-proof fiber, heat to 100-110° C. and react for 6-7 hours, cool to room temperature, wash with anhydrous ethanol and dry to obtain modified explosion-proof fiber.

[0031] Furthermore, in step C1, the dosage ratio of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, chloroform and thionyl chloride is 6.3-7.4 g: 50-60 mL: 8.5-9 mL.

[0032] Furthermore, the usage ratio of camphene, potassium thiocyanate and concentrated sulfuric acid in step C2 is 16.5-17.6 g: 10.3-11.2 g: 5-6 mL.

[0033] Furthermore, in step C3, the usage ratio of the intermediate 2, hydrazine hydrate and anhydrous ethanol is 10.4-11.2 g: 3.4-4.1 g: 100-120 mL.

[0034] Furthermore, in step C4, the molar ratio of intermediate 1 to intermediate 3 is 1:1, and the amount of potassium carbonate used is 10-15% of the mass of intermediate 3.

[0035] Furthermore, in step C5, the usage ratio of the intermediate 4, DMF and explosion-proof fiber is 2.3-3.2 g: 70-80 mL: 0.6-0.8 g, and the explosion-proof fiber is one of polypropylene fiber and polyethylene fiber.

[0036] Beneficial effects of the present invention: The present invention provides an environmentally friendly carbon-free dry material for a tundish, the raw materials of which include olivine, medium-grade sintered magnesia, lightly burned magnesia powder, magnesia, a binder, sodium hexametaphosphate, low-melting-point glass powder and modified explosion-proof glass. A new environmentally friendly binder is used to replace the solid phenolic resin, which does not produce or produces trace irritating gases during the baking process, does not introduce other impurities into the molten steel during continuous casting, does not collapse the package, and has the advantages of high strength, convenient construction, easy disassembly, long life and green environmental protection. Specifically, the active ingredients of the newly prepared binder are polysucrose / gelatin hydrogel composite material and hydrous sodium silicate. Polysucrose can form a network through its own physical and chemical reactions to make the material produce bonding strength. Hydrous sodium silicate contains crystal water and decomposes to form a small amount of alkaline solution during the baking process. A certain amount of hydrous sodium silicate has a great effect on the cross-linking condensation reaction of polysucrose. The polysucrose / gelatin hydrogel material-hydrated sodium silicate composite binder has high bonding strength, low price, non-toxicity, and harmlessness. It is an ideal intermediate dry material binder. In addition, for polysucrose / gelatin hydrogel, EDC molecules first activate the carboxyl groups on the gelatin molecules to form amino-reactive O-acylurea intermediates, which react with the amino groups on the gelatin molecules to form amide bonds. Then, the gelatin molecules are cross-linked to form a network structure. The gelatin and polysucrose molecules are mainly combined by physical action without any chemical bonding. A good hydrogen bond is formed between gelatin and polysucrose. The formed polysucrose / gelatin hydrogel is a cross-linked polymer that can swell in water and retain a large number of water molecules but cannot be dissolved. The dense network formed by the new binder makes the material produce bonding strength, and the decomposed water of gelatin and polysucrose during the heating process can also react chemically with magnesia to make the matrix strong.

[0037] In addition, the tundish dry material works at high temperature, and also bears the high-speed impact of molten steel injection flow to it while bearing the high temperature effect. Therefore, explosion-proof fiber is added in the raw material to prevent scouring and erosion, and the thermal shock resistance, scouring resistance and oxidation resistance of explosion-proof fiber are particularly important. Modified explosion-proof fiber is coated with a newly synthesized antioxidant to make it have excellent antioxidant function, thereby prolong the anti-aging ability of explosion-proof fiber and prolong the service life of substrate. Wherein, the components with antioxidant performance are hindered phenol and thiosemicarbazone, and camphene is used as raw material to synthesize thiosemicarbazone, and camphene compound itself has antioxidant activity, and some derivatives of thiosemicarbazone also have potential antioxidant effect simultaneously, and the protective effect of oxygen, heat, ozone, light, bending and copper damage is excellent, and hindered phenol generates stable phenoxy free radicals and cyclohexadienone peroxide in the auto-oxidation process, and has excellent non-discoloration and non-polluting property. Thiosemicarbazone and hindered phenol antioxidant cooperate with each other and act synergistically, and the heat-oxidation aging resistance of material is improved. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] The binder is prepared by the following steps:

[0041] Step S1, respectively preparing a gelatin aqueous solution with a mass fraction of 4% and a polysucrose aqueous solution with a mass fraction of 5%, weighing the two solutions, mixing them at 48°C, stirring for 30 minutes, standing and cooling at room temperature, placing them in an acetone solution containing 0.2% (w / v) EDC (the volume ratio of acetone to water is 9:1), taking them out after 48 hours, washing them with deionized water, and obtaining a preform, wherein the mixing volume ratio of the gelatin aqueous solution to the polysucrose aqueous solution is 3.5:1;

[0042] Step S2, uniformly mixing the preform obtained in step S1 with sodium metasilicate pentahydrate to obtain a binder, wherein the weight ratio of the preform to the sodium salt is 0.5:1.

[0043] Example 2

[0044] The binder is prepared by the following steps:

[0045] Step S1, respectively preparing a 5% gelatin aqueous solution and a 6% polysucrose aqueous solution by mass fraction, weighing the two solutions, mixing them at 49° C., stirring for 30 minutes, standing and cooling at room temperature, placing them in an acetone solution containing 0.2% (w / v) EDC (the volume ratio of acetone to water is 9:1), taking them out after 49 hours, washing them with deionized water, and obtaining a preform, wherein the mixed volume ratio of the gelatin aqueous solution to the polysucrose aqueous solution is 3.7:1;

[0046] Step S2, uniformly mixing the preform obtained in step S1 with sodium metasilicate nonahydrate to obtain a binder, wherein the weight ratio of the preform to the sodium salt is 0.6:1.

[0047] Example 3

[0048] The binder is prepared by the following steps:

[0049] Step S1, respectively preparing a gelatin aqueous solution with a mass fraction of 6% and a polysucrose aqueous solution with a mass fraction of 7%, weighing the two solutions, mixing them at 50° C., stirring for 30 minutes, standing and cooling at room temperature, placing them in an acetone solution containing 0.2% (w / v) EDC (the volume ratio of acetone to water is 9:1), taking them out after 50 hours, washing them with deionized water, and obtaining a preform, wherein the mixing volume ratio of the gelatin aqueous solution to the polysucrose aqueous solution is 4:1;

[0050] Step S2, uniformly mixing the preform obtained in step S1 with sodium metasilicate pentahydrate to obtain a binder, wherein the weight ratio of the preform to the sodium salt is 0.8:1.

[0051] Example 4

[0052] The modified explosion-proof fiber is prepared by the following steps:

[0053] Step C1, add 6.3 g of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 50 mL of chloroform into a three-necked flask, add 8.5 mL of thionyl chloride dropwise under nitrogen protection, raise the temperature to 48° C. after the addition is complete, react at this temperature for 6 hours, and distill under reduced pressure to obtain intermediate 1;

[0054] Step C2, add 16.5g of camphene and 10.3g of potassium thiocyanate into a three-necked flask, control the reaction temperature to 85°C, add 5mL of 75% concentrated sulfuric acid, react for 5h, cool, extract with ethyl acetate, wash with 0.5mol / L NaHCO3 solution, and recrystallize to obtain intermediate 2;

[0055] Step C3, add 10.4 g of intermediate 2, 3.4 g of 80% by mass hydrazine hydrate, and 100 mL of anhydrous ethanol into a three-necked flask, reflux for 35 min, cool and precipitate, and recrystallize from ethanol to obtain intermediate 3;

[0056] Step C4, adding intermediate 1, intermediate 3, potassium carbonate and toluene into a reactor, reacting for 5 hours at a speed of 200 r / min and a temperature of 60° C. to obtain intermediate 4, wherein the molar ratio of intermediate 1 to intermediate 3 is 1:1, and the amount of potassium carbonate is 10% of the mass of intermediate 3;

[0057] Step C5, add 2.3 g of intermediate 4 and 70 mL of DMF into a three-necked flask, mix well, add 0.6 g of polypropylene fiber, heat to 100° C. and react for 6 h, cool to room temperature, wash with anhydrous ethanol, and dry to obtain modified explosion-proof fiber.

[0058] Example 5

[0059] The modified explosion-proof fiber is prepared by the following steps:

[0060] Step C1, add 6.8 g of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 55 mL of chloroform into a three-necked flask, add 8.7 mL of thionyl chloride dropwise under nitrogen protection, raise the temperature to 50° C. after the addition is complete, react at this temperature for 6 hours, and distill under reduced pressure to obtain intermediate 1;

[0061] Step C2, add 16.9g of camphene and 10.8g of potassium thiocyanate into a three-necked flask, control the reaction temperature to 88°C, add 5.5mL of 75% concentrated sulfuric acid, react for 5h, cool, extract with ethyl acetate, wash with 0.5mol / L NaHCO3 solution, and recrystallize to obtain intermediate 2;

[0062] Step C3, add 10.9 g of intermediate 2, 3.9 g of 80% by mass hydrazine hydrate, and 110 mL of anhydrous ethanol into a three-necked flask, reflux for 38 min, cool and precipitate, and recrystallize from ethanol to obtain intermediate 3;

[0063] Step C4, adding intermediate 1, intermediate 3, potassium carbonate and toluene into a reactor, reacting for 7 hours at a speed of 250 r / min and a temperature of 65° C. to obtain intermediate 4, wherein the molar ratio of intermediate 1 to intermediate 3 is 1:1, and the amount of potassium carbonate is 12% of the mass of intermediate 3;

[0064] Step C5, add 2.7 g of intermediate 4 and 75 mL of DMF into a three-necked flask, mix well, add 0.7 g of polyethylene fiber, heat to 105° C. and react for 6 h, cool to room temperature, wash with anhydrous ethanol, and dry to obtain modified explosion-proof fiber.

[0065] Example 6

[0066] The modified explosion-proof fiber is prepared by the following steps:

[0067] Step C1, add 7.4 g of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 60 mL of chloroform into a three-necked flask, add 9 mL of thionyl chloride dropwise under nitrogen protection, raise the temperature to 52° C. after the addition is complete, react at this temperature for 7 hours, and distill under reduced pressure to obtain intermediate 1;

[0068] Step C2, add 17.6g of camphene and 11.2g of potassium thiocyanate into a three-necked flask, control the reaction temperature to 92°C, add 6mL of 75% concentrated sulfuric acid, react for 6h, cool, extract with ethyl acetate, wash with 0.5mol / L NaHCO3 solution, and recrystallize to obtain intermediate 2;

[0069] Step C3, add 11.2 g of intermediate 2, 4.1 g of hydrazine hydrate with a mass fraction of 80%, and 120 mL of anhydrous ethanol into a three-necked flask, reflux for 40 min, cool and precipitate, and recrystallize from ethanol to obtain intermediate 3;

[0070] Step C4, adding intermediate 1, intermediate 3, potassium carbonate and toluene into a reactor, reacting at a speed of 300 r / min and a temperature of 70° C. for 8 hours to obtain intermediate 4, wherein the molar ratio of intermediate 1 to intermediate 3 is 1:1, and the amount of potassium carbonate is 15% of the mass of intermediate 3;

[0071] Step C5, add 3.2 g of intermediate 4 and 80 mL of DMF into a three-necked flask, mix well, add 0.8 g of polypropylene fiber, heat to 110° C. and react for 7 h, cool to room temperature, wash with anhydrous ethanol, and dry to obtain modified explosion-proof fiber.

[0072] Example 7

[0073] An environmentally friendly carbon-free tundish dry material comprises the following raw materials by weight percentage: 17.4% olivine with a particle size of 3-5mm, 30% medium-grade sintered magnesia with a particle size of 1-3mm, 30% light-burned magnesia powder with a particle size of 0.5-1mm, 5% magnesia with a particle size of ≤0.08mm, 15% binder with a particle size of ≤0.08mm, 2% sodium hexametaphosphate with a particle size of ≤0.08mm, 0.5% low-melting-point glass powder with a particle size of ≤0.075mm, and 0.1% modified explosion-proof fiber with a length of 3-5mm.

[0074] The environmentally friendly carbon-free tundish dry material is made by the following steps:

[0075] Step A1, crushing the above raw materials;

[0076] Step A2, preparing ingredients according to the above formula;

[0077] Step A3, pouring the prepared dry material into the space between the outer wall of the tundish mold and the permanent village of the tundish, and forming it by self-flowing without vibration or ramming;

[0078] Step A4, baking at 100° C., and obtaining an environmentally friendly carbon-free tundish dry material after demoulding.

[0079] Example 8

[0080] An environmentally friendly carbon-free tundish dry material comprises the following raw materials by weight percentage: 20% olivine with a particle size of 3-5mm, 30% medium-grade sintered magnesia with a particle size of 1-3mm, 29.3% light-burned magnesia powder with a particle size of 0.5-1mm, 5% magnesia with a particle size of ≤0.08mm, 13% binder with a particle size of ≤0.08mm, 2% sodium hexametaphosphate with a particle size of ≤0.08mm, 0.5% low-melting-point glass powder with a particle size of ≤0.075mm, and 0.2% modified explosion-proof fiber with a length of 3-5mm.

[0081] The environmentally friendly carbon-free tundish dry material is made by the following steps:

[0082] Step A1, crushing the above raw materials;

[0083] Step A2, preparing ingredients according to the above formula;

[0084] Step A3, pouring the prepared dry material into the space between the outer wall of the tundish mold and the permanent village of the tundish, and forming it by self-flowing without vibration or ramming;

[0085] Step A4, baking at 170° C., and obtaining the environmentally friendly carbon-free tundish dry material after demoulding.

[0086] Example 9

[0087] An environmentally friendly carbon-free tundish dry material comprises the following raw materials by weight percentage: 20% olivine with a particle size of 3-5mm, 27.2% medium-grade sintered magnesia with a particle size of 1-3mm, 30% light-burned magnesia powder with a particle size of 0.5-1mm, 5% magnesia with a particle size of ≤0.08mm, 15% binder with a particle size of ≤0.08mm, 2% sodium hexametaphosphate with a particle size of ≤0.08mm, 0.5% low-melting-point glass powder with a particle size of ≤0.075mm, and 0.3% modified explosion-proof fiber with a length of 3-5mm.

[0088] The environmentally friendly carbon-free tundish dry material is made by the following steps:

[0089] Step A1, crushing the above raw materials;

[0090] Step A2, preparing ingredients according to the above formula;

[0091] Step A3, pouring the prepared dry material into the space between the outer wall of the tundish mold and the permanent village of the tundish, and forming it by self-flowing without vibration or ramming;

[0092] Step A4, baking at 220° C., and obtaining the environmentally friendly carbon-free tundish dry material after demoulding.

[0093] Comparative Example 1

[0094] Environmentally friendly carbon-free tundish dry material produced by Zhengzhou Sijihuo Refractory Materials Co., Ltd.

[0095] Comparative Example 2

[0096] The preparation method of the intermediate bag dry material of Comparative Example 2 refers to Example 7, except that no binder is added.

[0097] Comparative Example 3

[0098] The preparation method of the intermediate bag dry material of Comparative Example 3 refers to Example 7, except that no modified explosion-proof fiber is added.

[0099] The following performance tests were conducted on the tundish dry materials obtained in Examples 7-9 and Comparative Examples 1-3: (1) Testing the room temperature flexural strength and room temperature compressive strength after heat treatment at 220°C for 2h; (2) Testing the slag resistance: The experiment adopted a static crucible method, cutting the tundish dry materials after high temperature slag invasion in the middle, observing and measuring the depth of erosion and penetration of the tundish dry materials on the samples. The test results are shown in Table 1:

[0100] Table 1

[0101]

[0102] It can be seen from Table 1 that, compared with Comparative Examples 1-3, the tundish dry materials prepared in Examples 7-9 have better low-temperature baking strength and resistance to slag erosion and penetration.

[0103] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0104] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An environmentally friendly carbon-free tundish dry material, characterized in that: The raw materials include the following by weight percentage: 15% to 20% olivine with a particle size of 3-5mm, 20% to 30% medium-grade sintered magnesia with a particle size of 1-3mm, 18% to 30% light-burned magnesia powder with a particle size of 0.5-1mm, 5% magnesia with a particle size ≤0.08mm, 8% to 15% binder with a particle size ≤0.08mm, 2% sodium hexametaphosphate with a particle size ≤0.08mm, 0.5% low-melting point glass powder with a particle size ≤0.075mm, and 0.1 to 0.3% modified explosion-proof fiber with a length of 3-5mm.

2. The environmentally friendly carbon-free tundish dry material according to claim 1, characterized in that: The binder is prepared by the following steps: Step S1, respectively preparing a gelatin aqueous solution with a mass fraction of 4-6% and a polysucrose aqueous solution with a mass fraction of 5-7%, weighing the two solutions, mixing them at 48-50° C., stirring for 30 minutes, standing and cooling at room temperature, placing them in an acetone solution containing 0.2% (w / v) EDC (the volume ratio of acetone to water is 9:1), taking them out after 48-50 hours, and washing them with deionized water to obtain a preform; Step S2, uniformly mixing the preform obtained in step S1 with sodium salt to obtain a binder.

3. The environmentally friendly carbon-free tundish dry material according to claim 2, characterized in that: In step S1, the mixing volume ratio of the gelatin aqueous solution and the polysucrose aqueous solution is 3.5-4:

1.

4. The environmentally friendly carbon-free tundish dry material according to claim 2, characterized in that: In step S2, the weight ratio of the preform to the sodium salt is 0.5-0.8:1, and the sodium salt is one of sodium metasilicate pentahydrate and sodium metasilicate nonahydrate.

5. The environmentally friendly carbon-free tundish dry material according to claim 1, characterized in that: The modified explosion-proof fiber is prepared by the following steps: Step C1, add β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and chloroform into a three-necked flask, add dichlorothionyl dropwise under nitrogen protection, raise the temperature to 48-52° C. after the addition is complete, react at this temperature for 6-7 hours, and distill under reduced pressure to obtain intermediate 1; Step C2, add camphene and potassium thiocyanate into a three-necked flask, control the reaction temperature to 85-92° C., add 75% by mass of concentrated sulfuric acid thereto, react for 5-6 hours, cool, extract with ethyl acetate, wash with 0.5 mol / L NaHCO3 solution, and recrystallize to obtain intermediate 2; Step C3, add intermediate 2, hydrazine hydrate with a mass fraction of 80%, and anhydrous ethanol into a three-necked flask, reflux for 35-40 minutes, cool and precipitate, and recrystallize from ethanol to obtain intermediate 3; Step C4, adding intermediate 1, intermediate 3, potassium carbonate and toluene into a reaction kettle, reacting at a speed of 200-300 r / min and a temperature of 60-70° C. for 5-8 hours to obtain intermediate 4; Step C5, add intermediate 4 and DMF into a three-necked flask, mix well and then add explosion-proof fiber, heat to 100-110° C. and react for 6-7 hours, cool to room temperature, wash with anhydrous ethanol and dry to obtain modified explosion-proof fiber.

6. The environmentally friendly carbon-free tundish dry material according to claim 1, characterized in that: The preparation method comprises: Step A1, crushing the raw materials; Step A2, preparing ingredients according to the above formula; Step A3, pouring the prepared dry material into the space between the outer wall of the tundish mold and the permanent village of the tundish, and forming it by self-flowing without vibration or ramming; Step A4, baking at a temperature of 100° C.-220° C., and obtaining an environmentally friendly carbon-free tundish dry material after demoulding.